Implementasi Pendekatan Taktis Terhadap Hasil Keterampilan Bermain Sepak Takraw - Erland, Juliustian; Sucipto, Sucipto; Budiman, Didin (TEGAR: Journal of Teaching Physical Education in Elementary School, 2018)
This study discusses the implementation of a tactical approach to the results of sepak takraw playing skills for students of SDN 201 Sukaluyu Bandung. The research method to be used was an experimental method. The sampling technique in this study was purposive sampling. The sample in this study were 32 students. The instrument used was GPAI. The results of data analysis using paired sample t-test test, showed the significance value of the results of sepak takraw playing skills for students both in the experimental and control group classes of Sukaluyu Bandung Elementary School 201, as much as 0.000 0.05. Therefore, Ho is rejected, which means there are differences in the ability of class V students SDN 201 Sukaluyu Bandung in playing Sepak Takraw during before and after using a tactical approach and there is an influence on the ability to sepak takraw playing skills. AbstrakPenelitian ini mengkaji tentang implementasi pendekatan taktis terhadap hasil keterampilan bermain sepak takraw pada siswa SDN 201 Sukaluyu Bandung. Metode penelitian yang digunakan adalah metode eksperimen. Teknik pengambilan sampel dalam penelitian ini adalah Purposive sampling. Sampel dalam penelitian ini sebanyak 32 siswa. Instrument yang digunakan adalah GPAI. Hasil analisis data dengan menggunakan uji paired sample t-test, menunjukkan nilai signifikansi hasil bermain sepak takraw  pada siswa baik pada kelas eksperimen maupun kontrol di SDN 201 Sukaluyu Bandung, sebasar 0,000 0.05. Dengan demikian maka Ho ditolak, yang artinya terdapat perbedaan kemampuan siswa kelas V SDN 201 Sukaluyu Bandung dalam bermain Sepak Takraw antara sebelum dan setelah menggunakan pendekatan taktis dan terdapat pengaruh terhadap kemampuan bermain sepak takraw.